(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In the article ideas about the basic tasks of effective organization of biology lessons on the basis of modern pedagogical technologies, improvements of quality of education at interactive lessons in general educational system are given.